Development of Science Learning Media Based on Scientific Literacy For Elementary School Students - Barus, Maria; Simanjuntak, Tarida Alvina; Ndruru, Melita (Teunuleh Publisher, 2026)
This study aimed to develop science learning media based on scientific literacy using the Anyflip flipbook platform for elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The participants were 33 fifth-grade students from a public elementary school in Berastagi, Indonesia. Data were collected through expert validation sheets, student response questionnaires, and pre-test and post-test assessments. The results showed that the developed media was highly feasible, indicated by positive student responses with an average score of 87.27% in the very good category. The effectiveness test demonstrated an improvement in learning outcomes, with average scores increasing from 67.12 in the pre-test to 84.36 in the post-test. The N-Gain analysis showed that 24.24% of students were in the high category, 66.67% in the medium category, and 9.09% in the low category. These findings indicate that flipbook-based science learning media effectively improves students’ conceptual understanding, engagement, and scientific literacy in elementary science learning.